2017
DOI: 10.3847/1538-4357/836/1/78
|View full text |Cite|
|
Sign up to set email alerts
|

The Spectral Evolution of the First Galaxies. III. Simulated James Webb Space Telescope Spectra of Reionization-epoch Galaxies with Lyman-continuum Leakage

Abstract: Using four different suites of cosmological simulations, we generate synthetic spectra for galaxies with different Lyman continuum escape fractions (f esc ) at redshifts z ≈ 7-9, in the rest-frame wavelength range relevant for the James Webb Space Telescope (JWST) NIRSpec instrument. By investigating the effects of realistic star formation histories and metallicity distributions on the EW(Hβ)-β diagram (previously proposed as a tool for identifying galaxies with very high f esc ), we find that neither of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 87 publications
(117 reference statements)
1
89
0
Order By: Relevance
“…In this regard, recent progress has been made in the field of photo-ionization modeling (Jaskot & Oey 2013;Nakajima & Ouchi 2014;Zackrisson et al 2016;Inoue 2011), subsequently confirmed by observations (e.g., de Barros et al 2016;Vanzella et al 2016b;Verhamme et al 2016). In particular, line ratios in the rest-frame optical band like the O32 index ([Oiii]λ5007/[Oii]λ3727) and specific properties of the Lyα profile (Behrens et al 2014;Verhamme et al 2015;Dijkstra et al 2016) can provide valuable indirect probes of the physical state of the interstellar medium and of the column density of neutral gas (e.g., density-bounded or ionization-bounded), as well as the connection with the ultraviolet spectral slope, the Balmer emission lines and the Lyman continuum leakage (Zackrisson et al 2013(Zackrisson et al , 2016.…”
Section: Dynamical Mass Of Id11mentioning
confidence: 92%
See 1 more Smart Citation
“…In this regard, recent progress has been made in the field of photo-ionization modeling (Jaskot & Oey 2013;Nakajima & Ouchi 2014;Zackrisson et al 2016;Inoue 2011), subsequently confirmed by observations (e.g., de Barros et al 2016;Vanzella et al 2016b;Verhamme et al 2016). In particular, line ratios in the rest-frame optical band like the O32 index ([Oiii]λ5007/[Oii]λ3727) and specific properties of the Lyα profile (Behrens et al 2014;Verhamme et al 2015;Dijkstra et al 2016) can provide valuable indirect probes of the physical state of the interstellar medium and of the column density of neutral gas (e.g., density-bounded or ionization-bounded), as well as the connection with the ultraviolet spectral slope, the Balmer emission lines and the Lyman continuum leakage (Zackrisson et al 2013(Zackrisson et al , 2016.…”
Section: Dynamical Mass Of Id11mentioning
confidence: 92%
“…In addition, the rest-frame near-infrared wavelengths will be accessible with the JWST/MIRI camera. 4 Following the study of ID11 at z = 3.1169 by means of VLT/X-Shooter near infrared observations (see Vanzella et al 2016a), JWST spectroscopy will allow us to: (1) investigate the nature of the ionizing source from optical oxygen and Balmer lines ratios, in combination with ultraviolet features, (2) investigate the status of the interstellar medium through line ratios in the optical and ultraviolet rest-frame (e.g., by calculating the O32 index, and looking for density and/or ionization-bounded signatures), (3) look for the presence of outflows possibly from the nebular emission of high ionization lines (as we first attempted for ID11 with the Civλ1548, 1550 doublet), (4) perform direct estimates of the ionizing production rate from the Balmer lines, as well as to investigate the escaping ionizing radiation through indirect diagnostics calibrated at lower redshift (Vanzella et al 2016b), specifically proposed for the characteristics of JWST (e.g., Zackrisson et al 2013Zackrisson et al , 2016. It is worth noting that the current identification of photometric signatures of such nebular lines imprinted in the Spitzer/IRAC bands is even more complicated by the fact that at 5.5 z 6.6 both the 3.6µm and 4.5µm bands are polluted by Oxygen and Hα lines, respectively, introducing a degeneracy that prevents any clear measure of their equivalent widths (Smit et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…So in order to study f esc in the EoR, we need to link it to quantities that may be measured at very high redshifts. Nakajima & Ouchi 2014;Faisst 2016); (2) the strengths of nebular emission lines such as Hβ compared with the total star formation rate (Zackrisson et al 2013(Zackrisson et al , 2017; (3) the shape of the Lyα line profile (Verhamme et al 2015(Verhamme et al , 2017; or (4) the absorption strength of low-ionization lines and Lyman series lines, which are related to the covering fraction of absorbing gas (e.g., Heckman et al 2011;Leethochawalit et al 2016;Reddy et al 2016b). With the limited data we already have on our candidates, we can discuss the first two indicators, which we do in the following sections.…”
Section: Linking F Esc To Z>5 Observablesmentioning
confidence: 99%
“…Various indirect alternative approaches, including relations between the gas covering fraction and reddening (e.g., Jones et al 2012;Leethochawalit et al 2016;Reddy et al 2016), Hβ line equivalent width and UV spectral slope (Zackrisson et al 2013(Zackrisson et al , 2017, or analyses of the Lyα spectral line profile Verhamme et al 2017), have been proposed, but the values for the escape fraction remain within a fairly broad range: f 0.3 0.01 esc ion   . Additionally, measurements of the Thomson scattering optical depth to the CMB have placed the "galaxypopulation-averaged" ionizing escape fraction value within the range f 0.1 0.2 esc ion~-(e.g., Robertson et al 2015;Mitra et al 2016;Sun & Furlanetto 2016).…”
Section: Introductionmentioning
confidence: 99%